Nutrição mineral e produção de óleo essencial em plantações de corymbia citriodora fertilizado com composto orgânico de lodo de esgoto - Piazon Neto, Mario [UNESP] (Universidade Estadual Paulista (Unesp), 2012)
The sewage sludge is becoming an increasingly big problem for cities, with the population growing; there is an increased proportion of this material. An alternative for disposal this waste is the use in agriculture and forestry, with a special ability of the latter, since the end product is not intended for human or animal feeding. Based on this, is to find out if the treated sewage sludge (biosolids) has the ability to supply adequate nutrition for the cultivation of Corymbia citriodora (Hook.), a species of multiple uses, which highlights the essential oil extraction.This study aims to compare the fertilizing forests homogeneous species Corymbia citriodora for the production of essential oil with biosolids (2.5, 5.0, 10 and 20 ton / ha K), usual chemical fertilizer, only one treatment with potassium and an absolute control without any fertilization. Before the experiment be deployed under field conditions, there will be a soil test recommendations as a basis for mineral fertilizers. Several parameters will be evaluated every three months during one year, which will be the following: height, crown diameter, level of chlorophyll in leaves and leaf analysis and every six months will be done soil and leaf analysis. At the time of leaves collect, dry weight will be measured in addition to the oil yield and quality, quantifying the content of citronelal by the method of chromatography. There were statistical differences for height, crown diameter and index of green, and for crown diameter indicated differences from the first evaluation (after three months). For nutrition, chemical analysis of leaves was ...

O lodo de esgoto está se tornando cada vez mais um grande problema para as cidades, pois com o aumento populacional há proporcionalmente um aumento desse resíduo. Uma alternativa para a sua disposição é a utilização no setor agrícola e florestal, com uma maior aptidão para o último, pois seu produto final não se destina a alimentação humana ou animal. Visto isso, pretende-se saber se o lodo de esgoto tratado (Biossólido) tem a capacidade de fornecimento nutricional adequado para a cultura de Corymbia citriodora (Hook.), espécie de múltiplos usos, onde se destaca a extração de óleo essencial. Este trabalho teve por objetivo comparar a fertilização de florestas homogêneas da espécie Corymbia citriodora, destinadas à produção de óleo essencial, com biossólido, através dos seguintes tratamentos: 0; 2,5; 5,0; 10; 15 e 20 Mg ha-1 de biossólido complementado com potássio e boro, fertilização química usual, um tratamento apenas com potássio e boro e testemunha absoluta. Antes da instalação do experimento em campo, realizou-se análise química do solo como base para as recomendações da adubação química. Parâmetros biométricos e nutricionais foram avaliados a cada três meses durante um ano, como altura, diâmetro de copa, índice de cor verde nas folhas e análise foliar, além de realizar a cada seis meses a análise do solo. Ao fim de 12 meses, coletou-se as folhas do terço médio e inferior da árvore para a quantificação da biomassa. Além disso, foram retiradas amostras ...
Keywords: Essências e óleos essenciais; Solos - Fertilidade; Lodo de esgoto; Crescimento (Plantas); Essences and essential oils